Effect of MWCNT doping on the structural and optical properties of PVC/PVDF polymer blend - Abdelghany, A. M.; Meikhail, M.S.; Badr, S.I.; Momen, A. S. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Thin film samples of pristine polyvinyl chloride (PVC), poly vinyldine fluoride (PVDF) in combination with their blend in addition to samples containing factorial mass fraction of multi wall carbon nano-tubes (MWCNTs) in the dopant level were prepared via routine casting technique using tetrahydrofurane (THF) as a common solvent. X-ray diffraction and transmission electron microscopy (TEM) depict the nano-scale (15-25 nm) of functionalized MWCNTs with no surface damage results from functionalization process.X-ray diffraction (XRD) shows a semi-crystalline nature of PVDF with evidence for more than one phase namely a and b phases. The fraction of b phase was calculated and correlated to the dopant content. FTIR optical absorption spectra revels a preservation of the main vibrational bands before and after addition of MWCNTs in the doping level with a presence of new small band 1151 cm-1 assigned for the interaction and complexation between constituents.